2017
DOI: 10.3349/ymj.2017.58.4.878
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Closing Wedge Distal Femoral Osteotomy and Medial Reefing Procedure for Recurrent Patellar Dislocation with Genu Valgum

Abstract: PurposeRecurrent patellar dislocation is often associated with genu valgum. The purpose of this study was to analyze the short-term results of single-incision, closing-wedge distal femoral osteotomy (CWDFO) combined with medial reefing and lateral release for recurrent patellar instability with genu valgum.Materials and MethodsCombined CWDFO/medial reefing/lateral release was performed on 10 knees. Clinical evaluation was based on pre- and postoperative Knee Society Score (KSS) and Kujala patellofemoral score.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
49
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 22 publications
0
49
1
Order By: Relevance
“…This is because the valgus moment to the patella is reduced by decreasing the Q angle, and the congruity of the patella is thus Table 4 Results of patellofemoral joint congruity improved. However, these results deviate from our study, which showed that there is no effect on the patellar tilt or shift because combined procedures were proactively performed with DFO for patellar instability to improve patellar tracking, including tibial tuberosity osteotomy [23,26], medial reefing [23,25,26] and lateral release [23,26,27]. In our study, the mean preoperative tilt and shift were small at 5.1°and 6.8%, respectively, and there were no cases with patellar instability.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…This is because the valgus moment to the patella is reduced by decreasing the Q angle, and the congruity of the patella is thus Table 4 Results of patellofemoral joint congruity improved. However, these results deviate from our study, which showed that there is no effect on the patellar tilt or shift because combined procedures were proactively performed with DFO for patellar instability to improve patellar tracking, including tibial tuberosity osteotomy [23,26], medial reefing [23,25,26] and lateral release [23,26,27]. In our study, the mean preoperative tilt and shift were small at 5.1°and 6.8%, respectively, and there were no cases with patellar instability.…”
Section: Discussioncontrasting
confidence: 86%
“…In terms of the tilt and shift of the patella, there are some reports that suggest that DFO for patellar instability with valgus deformity of the knee may lead to significant improvement [23,[25][26][27]. This is because the valgus moment to the patella is reduced by decreasing the Q angle, and the congruity of the patella is thus Table 4 Results of patellofemoral joint congruity improved.…”
Section: Discussionmentioning
confidence: 99%
“…Those problems mentioned above could be resolved by DFO in the patients with associated genu valgum deformity.Traditionally, DFO was regarded as a surgical option for lateral tibiofemoral compartment osteoarthritis [27]. However, in recent years, it has been commonly accepted that correction of genu valgum could gain stabilization of the patella and reducing the risk of RPD by decreasing the forced shift towards the lateral side applied to the patella [11].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, many studies on this procedure have been reported. Chang et al [27] examined 10 patients who underwent CWDFO with lateral retinacular release and tightening of the medial retinaculum over an average follow-up period of 20 months. The postoperative KSS and Kujala scores were signi cantly improved.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 Distal femoral varus osteotomies have then been novelly described in the recent years to be successful in the management of patellofemoral instability. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] However, these publications are limited to case reports and small case series and no published literature have attempted to analyze them in totality. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] The current systematic review and meta-analysis aims to pool together these small case series to evaluate the outcomes and complications of distal varus femoral osteotomies when performed for patellofemoral instability.…”
mentioning
confidence: 99%